Safety and efficacy of Lactobacillus hilgardii CNCM I‐4785 and Lactobacillus buchneri CNCM I‐4323/NCIMB 40788 as a silage additive for all animal species. (30th October 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed was asked to deliver a scientific opinion on the safety and efficacy of a strain of Lactobacillus hilgardii and of Lactobacillus buchneri when used as a technological additive intended to improve ensiling at a proposed application rate of 3.0 x 10 8 colony forming units (CFU)/kg fresh material. The two bacterial species are considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. In previous opinions the identity of the strains has been clearly established and no antibiotic resistance of concern was detected. Therefore, the use of the strains as a silage additive is considered safe for livestock species, for consumers of products from animals fed the treated silage and for the environment. In the absence of data, no conclusion can be drawn on the skin and eye irritancy or skin sensitisation of the additive. The additive should be considered a potential respiratory sensitiser. In a previous application, three studies involving both strains used in combination at the same concentration were made with samples of whole crop maize with varied dry matter content. The same studies have been submitted in this application. The Panel reiterates its previous conclusions that Lactobacillus hilgardii CNCM I‐4785 and Lactobacillus buchneri NCIMB 40788/CNCM I‐4323 at 1.5 × 10 8 CFU of each active agent per kg of fresh forage, equivalent to 3 x 10 8 CFU total lactobacilli/kg of forage significantly improve the aerobic stability of the silage.